2004
DOI: 10.1007/bf02724090
|View full text |Cite
|
Sign up to set email alerts
|

Randomized control trial of quinine and artesunate in complicated malaria

Abstract: Artesunate is a much better drug than quinine in complicated malaria in terms of rapid coma resolution, fever clearance, parasite clearance and better tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…A study on 80 children with complicated malaria conducted in India showed the superiority of artesunate (42) over quinine (1). [183] In a recent study conducted in various regions of Asia, intravenous artesunate was significantly superior to the standard i.v. regime with quinine in the treatment of adult severe malaria.…”
Section: Artesunatementioning
confidence: 99%
“…A study on 80 children with complicated malaria conducted in India showed the superiority of artesunate (42) over quinine (1). [183] In a recent study conducted in various regions of Asia, intravenous artesunate was significantly superior to the standard i.v. regime with quinine in the treatment of adult severe malaria.…”
Section: Artesunatementioning
confidence: 99%
“…Seven trials reported fever clearance time, though three (8,11,12) presented data in a format that precluded meta-analysis; the remainder (9,(15)(16)(17) showed comparable results between all three artemisinin derivatives and quinine. All trials reported coma recovery time, though three (8,11,12) could not be included in meta-analysis.…”
Section: Risk Of Biasmentioning
confidence: 89%
“…The trials examined mortality, clinical outcomes (fever clearance time, coma recovery time, neurological sequelae), parasite clearance and some side effects. (Table II) was low for three trials (11,12,14), moderate for another three (8,10,17) and high for four trials (9,13,15,16). Only one trial(11) provided a sample size calculation.…”
Section: Current Best Evidencementioning
confidence: 96%
See 1 more Smart Citation
“…Coumarins constitute an important class of compound due to their presence as an important constituent of natural products [1] as well as their variety of medicinal applications such as anti-inflammatory [2], anti-convulsant [3], anti-viral [4], anticoagulent [5], antioxidant [6], antibacterial [7], antifungal [8], anti-HIV [9], anti-carcinogenic material [10] and as antihistamine [11]. Besides the wide spectrum biological applications of coumarin and its derivatives the chemical literature also embodies their some applications from the material view point such as cosmetics [12], optical brightening agents [13], and laser dyes [14].…”
Section: Introductionmentioning
confidence: 99%